Extending Classroom Learning Borders - Adriana C. Salvia; Nazlin Z. Hirji; Het Daxeshbhai Shah; Sandra Devlin Cop; Sue D. L'Europa (Journal of Innovation in Polytechnic Education)
Through the provision of education and training, the Caregiver Training Workshop (CTW) pilot study aimed to advance knowledge about in-person educational interventions for primary family caregivers aiding ill adults (18 years of age and over) at home. The target population was community-dwelling chronic disease caregivers, fourteen of whom participated in the workshop/pilot study in September and October 2019. The sessions were offered once a week, over five weeks—each session lasting two hours. The goal of the CTW pilot study was to measure any relationship between caregiver burden levels and the study’s multi-component curriculum and course design, and to obtain participant feedback about the content and structure. Curricular topics were selected based on a review of the literature. The methodology selected was mixed-methods and convergent pretest–posttest design. Data was collected at three points in time. The pre-workshop data collection instruments consisted of the Burden Scale for Family Caregivers (BSFC) in long form and a mixed demographics form. Post-workshop instruments consisted of the BSFC (second time) and open-ended questions evaluating the program. Three-months post workshop conclusion, the instruments consisted of the BSFC (final time) and a mixed questionnaire regarding the program’s impact. The reduction in caregiver burden was not statistically significant; however, burden scores from three of the 14 caregivers improved over the study period. Analyzing the qualitative data, as well as viewing caregiver burden through self-efficacy theory, offer insights as to why. Many caregivers expressed interest in maintaining contact with each other post workshop completion. This supports research indicating that some caregivers are interested in maintaining social connections throughout their care recipients’ illness trajectories.